Using a person-centered approach to identify patterns of exposure to intimate partner violence and child abuse in women: associations with mental health - Free, Bre’Anna L. (Child maltreatment, 2021)
Patterns of exposure to intimate partner violence (IPV) and child abuse (CA) were explored in 467 women seeking psychological assistance following IPV. Using latent class analysis, three classes were obtained: women who had experienced physical, sexual, and psychological IPV, along with childhood physical and sexual abuse (IPV + CA; 38.5%); women who had experienced physical, sexual, and psychological IPV only (IPV/no CA; 52.9%); and women who had experienced psychological IPV only (Psych IPV only; 8.6%). Associations of class membership with severity of specific mental health conditions were examined, along with the number of diagnosed conditions. Significant between-class differences were noted on severity of IPV-related posttraumatic stress disorder, depressive disorders, alcohol and substance use disorders, and social phobia. Classes also differed significantly on the number of mental health conditions. Understanding patterns of betrayal-based trauma (e.g., IPV and CA) can inform care within agencies that serve IPV survivors by highlighting individuals at-risk for mental health conditions.